The Role of Language in Shaping Cultural Identity (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Language is a fundamental aspect of human culture, serving as a primary means of communication and a key component in the formation of cultural identity. This article explores the multifaceted role of language in shaping and expressing cultural identity. By examining linguistic diversity, the relationship between language and thought, and the impact of language on social cohesion and cultural continuity, we aim to highlight the profound influence language has on individuals and communities. Through this analysis, we underscore the importance of preserving linguistic diversity as a means of maintaining cultural heritage and promoting intercultural understanding.